Enhancing EFL learner’s speaking skill through Classroom Interaction The cas of first year LMD students of English at Amar Telidji University of Laghouat. - BENGHERIGA ,Mohamed; HACHANI, Ismail Saad Messaoud; HAMADI ,Nabil Aziz (Faculty of Letters and Foreign Languages Department of English, 2017)
The present study aims at exploring the connection between classroom interaction and the development of learners’ speaking abilities. It investigates the possibility of promoting learners’ speaking skill. This research attempts to inquire the effectiveness of classroom interaction as a pedagogical strategy in enhancing EFL learners speaking performance as well as promoting their capacity to produce new language. As student-researchers in the classroom, we have hypothesized that if EFL learners are provided with opportunities to experience producing L2 in the classroom, then their speaking skill will improve. The investigation takes first year LMD students of English at Amar Telidji University of Laghouat. In order to achieve the preceding aims, a descriptive exploratory study is carried out. The main data gathering tools in this study are questionnaires of both teachers and learners as a case study. The questionnaires were administered to a sample of forty EFL students and five teachers of oral expression of first year classes at Amar Telidji University of Laghouat. To determine the relationship between classroom interaction and students’ speaking progress, the results obtained from the students’ and teachers’ questionnaires are analyzed. The results of the questionnaires reveal a positive relationship between the two variables and show the ways in which classroom interaction significantly promotes learners’ speaking performance